Penerapan Multiplekser Analog Untuk Implementasi Sistem Modulasi Biner - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRAK Digital modulation may be viewed as one-to-one mapping, from digital code domain to modulated waveform domain. Each digital code has its corresponding modulated waveform. When a code enters modulator, the modulator generates a spesific modulated waveform which is matched with that code. Refering to this view, the digital modulator circuits may be constructed based on multiplexer devices. This research implemented a hardware model of a binary modulator circuit using an analog multiplexer. The modulation techniques which can be performed are binary amplitude shift keying (BASK), binary frequency shift keying (BFSK), and binary phase shift keying (BPSK). The result of this research informs that multiplexer-based modulator simplifies the design, implementation, and operation procedure of the digital modulator circuit, but it needs more supporting circuits than the multiplier-based modulator. The circuit operates properly: the BASK, BFSK, and BPSK function can be performed. Performance of the circuit has not been tested. Keywords: modulasi biner, multiplekser